Enhancing interprofessional education readiness in undergraduate dental students: a scenario-based peer learning programme - Gül Çelik; Ömer Faruk Sönmez; Aysel Başer (BMC, 2024)
Abstract Background Interprofessional Education (IPE) is an educational approach that brings together students from different healthcare professions to foster collaborative learning and teamwork. Before integrating IPE into the curriculum of health preprofessional students, it is necessary to increase their readiness for IPE. Dentistry increasingly values interprofessional collaboration and teamwork for enhanced patient care and healthcare team competencies, an emphasis also echoed by recent dental education authorities. The aim of this quasi-experimental research was to assess the influence of Scenario Based Learning Peer Learning (SBPL) programme, which involved scenarios necessitating interprofessional communication, on the readiness for IPE among a cohort of undergraduate dental students studying within the framework of the European Higher Education Area (EHEA). Methods This study investigates undergraduate dental students' readiness for IPE and the influence of SBPL programme on their readiness. Participants (n = 25) from 18 EHEA countries completed the Readiness for Interprofessional Learning Scale (RIPLS) before and after SBPL programme, held at the 70th European Dental Students' Association (EDSA) meeting. Data were analyzed using the Wilcoxon Signed Rank Test (p = 0.05). Results After the SBPT programme, there was a statistically significant increase (p < 0.05) in the mean of the total scale, teamwork and collaboration, roles and responsibilities and professional identity subscale. In general, SBPL programme showed a constructive effect on interprofessional readiness. Although there was no statistically significant increase only in items 9,12,18 of the 19 items of the RIPLS, there was an increase in the averages in all except item 12. Conclusion Our research emphasizes the importance of diverse perspectives and IPE in the realm of dental education. Within the limits of this study, it showcases the efficacy of a brief half-day SBPL programme with interprofessional scenarios in enhancing participants' readiness. The programme notably enhanced dental students' readiness in grasping crucial aspects of IPE: teamwork and collaboration, professional identity, and roles and responsibilities. However, this study does not delve into the potential impact of a comprehensive, long-term curriculum integrating IPE principles. This gap underscores the need for further exploration into the sustained influence of IPE on the interprofessional skills of dental school graduates.